“Perspektif Ibu Terhadap Penyakit Infeksi Diare Pada Balita “ Studi Kualitatif di Puskesmas Mananga, Kecamatan Mamboro Desa Wendewa Utara Kabupaten Sumba Tengah - Jawang, Eriska Peku; Sanubari, Theresia Pratiwi Elingsetyo; Kinasih, Angkit (Jurnal Keperawatan Muhammadiyah, 2019)
Infectious diseases is a very dangerous disease, especially in children under 5 years old. Diarrhea be one of infectious diseases that the commonly encountered. It is estimated that more than 10 million children were less than 5 years die each year where around 20% die of infections diarrhea. Progress in reducing diarrheal diseases influenced by the perception of attitudes and knowledge of every member of society, especially mother perspective because its important role in the prevention and process treatment of diarrheal diseases. The objective  of this study is  to determine mother perspective of diarrhea on children under 5 years old in central Sumba. This study used a qualitative research design with in-depth interview. Number of research participants whor  mothers. Research location was in of North Wendewa Village, Mananga Health Center in Central Sumba District.  Results:  The mother's perspective on diarrheal infection is influenced by factors such as lack of knowledge, maternal behavior, economy, environment and health services. Conclusion: The formation of a mother's perspective  are influenced by factors such as lack of knowledge, level of education, as well as lack of sources of information obtained from various media and resulting in maternal behavior in dealing with infectious diseases. The others caused by low economic factors, inadequate environment and health services.